Determination of relative tectonic activity of faults controlling Varto Basin (Muş) by geomorphic indices - Avci, Vedat; Sunkar, Murat (Gumushane University, 2023)
In this study it is aimed to determine the relative tectonic activity of faults controlling Varto Basin with geomorphic indices. Varto Basin is located in the southeast of Karlıova, between Bingöl and Serafettin Mounts. Varto Fault, which intersects with the East Anatolian Fault in Karlıova and the continuation the North Anatolian Fault towards southeast, has been effective in the formation of the basin. Being right lateral strike slip, Varto Fault starts in the east of Karlıova Triple Junction and continues towards southeast in the form of a zone. Due to this location, tectonic activity in and around the basin is very high. The young tectonic movement of the basin has been revealed by geomorphic index analysis method. In these analyses, digital elevation model (DEM), stream, fault and geology data were used as the basic data set. A total of 43 sub-basins reflecting tectonic activity have been identified around the basin periphery and on Varto Fault zone (VFZ). For this purpose, hypsometric integral (Hi), hypsometric curve (Hc), basin asymmetry factor (AF), drainage basin shape (Bs), stream length-gradient index (SL), channel sinuosity (S) and elongation ratio (Re) analyses were performed. Along with the basin analyses, the measurements of mountain front sinuosity ratio (Smf) and valley floor width-to-valley height ratio (Vf), which are frequently used in the determination of active tectonics, and streams longitudinal profile analyses were done in the basin. According to the results of the analyses, tectonic activity classes of the basins were determined and their distributions were shown. According to these results, except for the two basins in the south of the Varto basin and one located in the VFZ, all others fall into very high and high tectonic activity classes. Index results, earthquakes, hot and cold sources along the fault zone and geomorphological figures prove that active tectonics are intense in and around Varto Basin. © 2023, Gumushane University. All rights reserved.
Jeomorfik indislerle Varto Havzası’nı (Muş) denetleyen fayların göreceli tektonik aktivitesinin belirlenmesi
Keywords: Geomorphic indices; Relative tectonic activity; Varto Basin; Varto Fault Zone (VFZ)